Personality Styles and Mental Health Challenges in University Students - Jawairia Saleem, Anam Iftikhar, Sadia Saleem, Sadia Majeed, Asma Siddiqui, Qurat.Ul.Ain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To explore the relationship between different personality styles and mental health issues which students faced in university Study Design: Correlation Placement and duration: December 2018 to December 2020 in Private and government universities of Lahore. Methodology: The total sample comprised 300 participants with the age range of 19 -25 years (M=19. 94, SD=1. 63). Two measures were used, namely the Big Five Inventory (BFI) and Student Problem Checklist (SPCL) Results: According to current research, it was revealed that there was a significant relationship between types of personality and mental health issues. Neurotic individuals were faced with more mental issues than others. Sense of dysfunction had a positive significant relationship with lack of Confidence, Self-Regulation, and Anxiety proneness. Conclusion: it is essential to study personality types and mental health relationships because after knowing the relationship guidance and awareness can be developed in guardians. Keywords: styles of personality, Mental health Issues, University Students.